PExIL: Programming Exercises Interoperability Language - Queirós, Ricardo (2011)
Several standards appeared in recent years to formalize the metadata of learning objects, but they are still insufficient to fully describe a specialized domain. In particular, the programming exercise domain requires interdependent resources (e.g. test cases, solution programs, exercise description) usually processed by different services in the programming exercise life-cycle. Moreover, the manual creation of these resources is time-consuming and error-prone leading to what is an obstacle to the fast development of programming exercises of good quality. This paper focuses on the definition of an XML dialect called PExIL (Programming Exercises Interoperability Language). The aim of PExIL is to consolidate all the data required in the programming exercise life-cycle, from when it is created to when it is graded, covering also the resolution, the evaluation and the feedback. We introduce the XML Schema used to formalize the relevant data of the programming exercise life-cycle. The validation of this approach is made through the evaluation of the usefulness and expressiveness of the PExIL definition. In the former we present the tools that consume the PExIL definition to automatically generate the specialized resources. In the latter we use the PExIL definition to capture all the constraints of a set of programming exercises stored in a learning objects repository.